Margins of Moral Character in Aristotle: Dream and Brutishness; [Márgenes del Carácter Moral en Aristóteles: Sueño y Bestialidad] - Aoiz-Monreal, F (Universidad Nacional de Colombia, 2022)
Plato points out in Republic ix that in all human beings there is a background of bestial desires that manifest especially in dreams and the wise man manages to keep away. The article tries to reconstruct Aristotle’s response to these theses through the study of three topics of his philosophy: the concept of happiness, the category of bestiality, and the etiology of dreams developed in the treatises on dreams included in Parva Naturalia. © 2022 Universidad Nacional de Colombia. All rights reserved.
Keywords: Aristotle; brutishness; moral character; psychopathologies; dream